IMF Staff papers : Volume 44 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1997)
This paper deals with liberalization and the evolution of output during the transition from plan to market. It explains why strong liberalization leads to a comparatively steep fall in output early in the transition, but a relatively strong recovery later on. Because it takes time to restructure the capital stock inherited from the old system, liberalization initially leads to transitional unemployment of capital and the contraction of the old enterprise sector. By making room quickly for the new, more efficient enterprises, however, liberalization also sets the stage for recovery and a much higher level of income in the medium term. [JEL E23, P21, P27, P52].